Microcontroller-based inverter topology integrated in PV systems. Issue 1 (5th January 2015) - Ahmed Masmoudi, Dr; Bouzguenda, Mounir; Selmi, Tarek; Gastli, Adel; Masmoudi, Ahmed
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to study the problem of the leakage currents in transformerless inverter topologies. It proposes a novel topology and how important the adopted control strategy on the power quality produced by the inverter. Design/methodology/approach – The paper presents an investigation of a novel transformerless inverter topology. It adopted a control strategy in which the DC source is disconnected from the inverter when the zero vectors of the control are applied. By using such control strategy, the electrical efficiency of the whole system was improved and the leakage current was significantly reduced. Findings – The paper provides a solution to minimize the leakage current in transformerless inverter topologies. Besides, the problem of zero-crossing distortions was totally eliminated. Research limitations/implications – Because of the high conversion ratio of the boost converter, the efficiency of the whole system needs to be enhanced. Practical implications – The paper includes the experimental results of the proposed topology which are in good match with the simulation results. Originality/value – This paper identifies a need to study the leakage current phenomena in transformerless inverter topologies.